Bioethics and human development for a culture of peace - Llanos Zuloaga, Martha (2008)
The autores on the base of her professional training a human development research and her wide experience as a psychologist, share reflections on Bioethics Human rights, which recognizes the importanceof evaluating social realities and achievieving fairness, paying attention to women´situation, to population of developing countries, indigenous communities and vulnerable population.